Long shadows of the walking dead on economic activity - N. Nergiz Dincer; Pelin Pektekin; Ayça Tekin-Koru (Central Bank Review (CBR), 2023)
This paper presents the panorama of zombie firms in the Turkish economy, which are highly inefficient, highly indebted firms that have low or sometimes negative productivity, and provides an analysis of the impact of these firms on economic activity for the period 2012-2015. Our results suggest that the number of zombie firms in Türkiye has increased. The share of these firms in sales and employment has also increased, but at a lower rate. These firms are mainly found in low-technology manufacturing and transportation and distribution services. The paper also shows that healthy firms increase total factor productivity, employment growth, and the investment-to-capital ratio in the economy in a robust manner. The sales of zombie firms have no distorting effect on the economic activity of healthy firms. However, capital sunk into zombie firms has a differential impact on the performance of healthy firms. When the share of zombie capital in a sector increases, the TFP growth of manufacturing firms decreases, while the employment growth of medium-sized service firms increases.
Keywords: D22; D24; E24; C55; 330; Zombie firms; Productivity; Micro data; Türkiye